Dickens : entre système organique et hémorragie textuelle - Nathalie Jaëck (Cahiers Victoriens et Edouardiens)
In this paper I propose to show that Dickens’s novels are characterised by a double and contradictory impulse. On the one hand, they attempt to build a closed system, a textual web, able to provide the reader with a full, finite, faithful, and authoritative picture of reality, and in this line, Dickens created the most successful XIXth century literary ideosphere. But on the other hand, Dickens constantly strives to destabilise his own system, to open breaches, and lines of escape, to create proliferating, virtually uncontrollable outbursts. The text leaves way to its own contradiction, it undoes and destabilises its own paradigms, and questions its own realist literary stance, through strategies of interruption, digressions and diversions, until the dissident text actually competes with the official one, notably in Great Expectations and Bleak House.